Race / Ethnicity and Outcomes Following Inpatient Rehabilitation for Hip Fracture - Graham, James E. (2008)
BACKGROUND: Hip fracture results in severe and often permanent reductions in overall health and quality of life for many older adults. As the U.S. population grows older and more diverse, there is an increasing need to assess and improve outcomes across racial/ethnic cohorts of older hip fracture patients. METHODS: We examined data from 42,479 patients receiving inpatient rehabilitation for hip fracture who were discharged in 2003 from 825 facilities across the U.S. Outcomes of interest included length of stay, discharge setting, and functional status at discharge and 3-to-6-month follow-up. RESULTS: Mean age was 80.2 (sd = 8.0) years. A majority of the sample was non-Hispanic white (91%), followed by non-Hispanic black (4%), Hispanic (4%), and Asian (1%). After controlling for sociodemographic factors and case severity, significant (p < .05) differences between the non-Hispanic white and minority groups were observed for predicted lengths of stay in days [95%CI] (Asian: 1.1 [0.5–1.7], non-Hispanic black: 0.8 [0.6–1.1]), odds of home discharge (Asian: 2.1 [1.6–2.8], non-Hispanic black: 2.0 [1.8–2.3], Hispanic: 1.9 [1.6–2.2]), lower discharge FIM ratings (non-Hispanic black: 3.6 [3.0–4.2], Hispanic: 1.6 [0.9–2.2] points lower), and lower follow-up FIM ratings (Hispanic: 4.4 [2.8–5.9]). CONCLUSIONS: Race/ethnicity differences in outcomes were present in a national sample of hip fracture patients following inpatient rehabilitation. Recognizing these differences is the first step towards identifying and understanding potential mechanisms underlying the relationship between race/ethnicity and outcomes. These mechanisms may then be addressed to improve hip fracture care for all patients.